PJMHS 2021
DOI: 10.53350/pjmhs211592272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brain Training Game on Mild Cognitive Impairment (MCI) in Older Adults

Abstract: Aim: To determine effects of Kinect- based games on neurocognitive functions in older adults with mild cognitive impairment. Methodology: A quasi experimental pre-post trail was conducted on 18 mild cognitive impairment (MCI) older adults. The subjects were recruited to access cognitive impairment through purposive sampling technique. The inclusion criteria were elderly aged ≥ 50 years, both genders, able to read and write, whereas older adults with severe cognitive impairments, neurological disorders and un c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Furthermore, cognitive improvement was evident in an intervention MCI group whose participants played digital (on screen) and traditional (in groups) games, such as memory games e.g., remembering the sequence and colour of balls presented on the screen, coordination and emotional games, solitaire, puzzles, and board games in 8 weeks [65]. Also, people with MCI were able to improve their cognitive processes with the video game 'Body and Brain Exercises' which focused on brain training of logic and reasoning, physical skills, memory, body reflexes and math calculations [66]. Therefore, the previous studies may support the cognitive improvements in our study and show evidence that the use of the COSMA games may positively affect cognitive skills when these are being played regularly in MCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cognitive improvement was evident in an intervention MCI group whose participants played digital (on screen) and traditional (in groups) games, such as memory games e.g., remembering the sequence and colour of balls presented on the screen, coordination and emotional games, solitaire, puzzles, and board games in 8 weeks [65]. Also, people with MCI were able to improve their cognitive processes with the video game 'Body and Brain Exercises' which focused on brain training of logic and reasoning, physical skills, memory, body reflexes and math calculations [66]. Therefore, the previous studies may support the cognitive improvements in our study and show evidence that the use of the COSMA games may positively affect cognitive skills when these are being played regularly in MCI.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering that there are not many serious games for people with MCI which are validated in literature, the COSMA application achieved the advancement of showing proof that people with MCI can use it and benefit from it. In addition, the intervention in this study was established in 4 weeks' time and this may highlight the efficiency of COSMA with respect to other serious games and digital interventions which showed cognitive improvement in MCI from 8 weeks to 6 months of use [19], [59], [64]- [66].…”
Section: Discussionmentioning
confidence: 99%
“…Also, 344 citations were identified and screened from additional sources, including Google Scholar, reference searching, and others. We initially found 26 potential citations for full-text evaluation and finally included 19 articles in this scoping review [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Data Synthesismentioning
confidence: 99%
“…An overview of the included studies is provided in Table 2. The vast majority of studies, 84% (n = 16), were conducted in India [32][33][34][35][36][37][38][39][40][41][42][43][44][45]48,49], and the remaining studies (n = 3) were conducted in Pakistan [31,46,47]. No studies were identified from Afghanistan, Bangladesh, Bhutan, Maldives, Nepal, and Sri Lanka.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation